Pentahelix Model Collaboration In Disaster Risk Reduction Efforts In Bintan Regency - Suherry, Suherry; Husni, Alfi; Ferizone, Ferizone; Rifa'i, Azwan; Barus, Muhamad Anugrahi (Universitas Riau Kepulauan, 2026)
This study aims to examine the collaborative dynamics of the Pentahelix model in disaster risk reduction efforts in Bintan Regency. The study is grounded in the high disaster vulnerability of the region, including floods, extreme weather, high waves, coastal abrasion, forest and land fires, and drought. This research employs a qualitative approach, with data collected through in-depth interviews, Focus Group Discussions (FGDs), and document analysis, including the 2022–2026 Disaster Risk Assessment. The findings reveal that the five main actors in the Pentahelix model, namely government, academia, business sector, media, and community, actively participate in disaster risk reduction forums with different but complementary roles. The government acts as regulator and coordinator, academia contributes scientific knowledge, the business sector supports logistics and Corporate Social Responsibility (CSR) initiatives, media disseminates disaster information, and communities implement local preparedness strategies. The study identifies a sharing power pattern among actors, demonstrating that disaster risk reduction responsibility is distributed across sectors rather than centralized in government. Theoretically, these findings extend the Pentahelix model by demonstrating that disaster risk reduction collaboration is not only based on role distribution but also on adaptive power-sharing among actors, particularly in archipelagic and disaster-prone regions, thereby enriching collaborative governance theory in disaster management contexts. In conclusion, the Pentahelix model is relevant for strengthening disaster resilience in Bintan Regency through integrated local resources and capacities. However, this study is limited by its territorial scope and lack of long-term impact analysis. Future research is recommended to conduct comparative studies in other archipelagic regions and explore technological innovation and digital media in enhancing community resilience.